Correlation between quality of life and spirituality in geriatrics (Annals of Medical Research, 2021)
Aim: When tackling with human health, the elderly, one of the society’s most vulnerable groups, must be analyzed in all its aspects. It was thought that spirituality had an important role in human health and fight against diseases. There is a scarcity of data reported from the literature on spirituality and health. Therefore, this study was undertaken to determine the impact of quality of life and spirituality on geriatrics.Material and Methods: This research was made as descriptive research. The sample consisted of 368 individuals over 65 registered, who were being followed up at 10 Primary Care Clinics of Malatya province. Data were collected using an individual questionnaire, WHO QOL Instrument Elderly Module and Spiritual Orientation Scale.Results: A statistically significant difference was determined between the income status, situations of living together, having support, having chronic illnesses and using devices and the spiritual orientations of the participants. When the sociodemographic characteristics and quality of life score averages of the geriatrics were compared, a statistically significant difference was determined between age, educational level, chronic illnesses, physical disability and using devices (p0.05). When the ages of the geriatrics and their quality of life score averages are compared, it is seen that the sensory functions score of the elder individuals whose ages are between 85-94 is 10.69±2.17. It was determined that the men’s quality of life subdimensions average score was higher than the women’s. A significant difference was determined in the quality of life averages of the participants who did not have chronic illnesses. When the correlation between the total quality of life and their spirituality score averages was considered, a statistically significant correlation in the positive direction was determined (r=.21, p=.000).Conclusion: Our results suggest that there was a positive correlation between the quality of life and spirituality in geriatrics and quality of life increased as the spirituality increased in geriatrics.Keywords: Spirituality; quality of life; health professionals; elderly.
Keywords: Spirituality; quality of life; health professionals; elderly.